Hepatic Malignancy in an Infant with Wolf–Hirschhorn Syndrome. (4th May 2017) - Rutter, Sara; Morotti, Raffaella A; Peterec, Steven; Gallagher, Patrick G.
ABSTRACT: Introduction : Wolf–Hirschhorn syndrome (WHS) is a contiguous gene syndrome involving deletions of the chromosome 4p16 region associated with growth failure, characteristic craniofacial abnormalities, cardiac defects, and seizures. Case Report : This report describes a six-month-old girl with WHS with growth failure and typical craniofacial features who died of complex congenital heart disease. Genetic studies revealed a 9.8 Mb chromosome 4p-terminal deletion. At autopsy, the liver was grossly unremarkable. Routine sampling and histologic examination revealed two hepatocellular nodular lesions with expanded cell plates and mild cytologic atypia. Immunohistochemical staining revealed these nodules were positive for glutamine synthetase and glypican 3, with increased Ki-67 signaling and diffuse CD34 expression in sinusoidal endothelium. These findings are consistent with hepatoblastoma or hepatocellular carcinoma. Conclusions : A possible association between WHS and hepatic malignancy may be an important consideration in the care and management of WHS patients.